MUJERES Y DERECHOS - Torrez Díaz, María Concepción (2020)
Data on violence against women in Spain are unbearable for an advanced democratic state, which allows inferring that there is a social/sexual reality prior to the social coexistence pact that is discriminatory for women and threatens their fundamental rights. This reality of preexisting subordination to the norms of social coexistencehas been based (and sustained) on the asymmetry of socio/sexual power that pivots in the sex/gender system. Hence the need to provide the “gender” category with constitutional relevance.Women and rights - Feminist legal theory - Anti-discrimination law and equality - Constitutional guarantees - Gender violence - Structural discrimination - Sex/gender system - Gender perspective - Legal methodology